St. Bartholomew’s Night Soviet style: The history of the idiom in the 1900s–1930s - N. V. Petrov; N. S. Petrova (Шаги)
The paper deals with the anatomy of the idiom “St. Bartholomew’s Night” and the reasons for its popularity in the context of pre-revolutionary and early Soviet history. It analyzes the rumors of this era about a forthcoming “St. Bartholomew’s Night” and determines their place in the auditory response to significant sociopolitical transformations of the early 20th century. Since the middle of the 19th century the expression “St. Bartholomew’s Night” is found in journalism, historical literature, school textbooks, etc., and is then actively used in leftist political discourse of the early 20th century to negatively characterize the tsarist regime. In Bolshevik rhetoric the idiom is found in threats to political opponents. “St. Bartholomew’s Night” covers a series of events and generates a network of meanings associated with the discursive practices of competing political, ethnic and confessional groups. The reaction during the period of the Civil War and the first Soviet years to such public texts and speeches is expressed in mass panics in connection with the expected reprisals against various social, ethnic, and confessional groups. Rumors from the 1920s and 1930s about “St. Bartholomew’s Night” fit perfectly into the general context of early Soviet eschatological moods, when the post-revolutionary breakdown of the usual order actualized notions of the end times. Rumors appear in mass discourse in an order that corresponds to the key changes in the sociopolitical agenda of the first decades of the twentieth century. This shows how public anxiety is expressed and the problem of the conflictual division of society.